Meningkatkan Layanan Publik melalui Smart Governance: Analisis Informasi, Pelayanan, Efisiensi A'Kio Smart City di Kabupaten Gowa - Fitri, Anisa; A, Muhammad Rizal; Sakawati, Herlina; Sulmiah, Sulmiah; Widyawati, Widyawati (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
This study explores the implementation of innovative governance through the A'Kio smart city platform in the Gowa Regency, focusing on efficiency, information, and public services. A qualitative descriptive approach was used, with data collected through interviews and observations. The findings indicate that the A'Kio Smart City platform enhances government operational efficiency by optimizing human resources and accelerating public administration processes. The platform provides accurate and relevant information sourced directly from government agencies. However, challenges were identified regarding the regular update of information, which can affect data relevance. The quality of services the platform offers is good, with easy access and clear information, though employee responsiveness, especially to public requests, requires improvement. Additionally, limited socialization has resulted in insufficient public awareness of the platform's existence and benefits. This study highlights the need for regular updates, a more user-friendly interface, and improved socialization strategies.